Takotsubo syndrome - I. A. Latfullin; Z. F. Kim (Кардиоваскулярная терапия и профилактика)
The paper presents the studies of the Takotsubo syndrome – reversible local or diffuse myocardial hypokinesis, with clinical and electrocardiografical patterns of acute myocardial infarction, and elevated levels of cardio-specific enzymes without myocardial ischemia or reperfusion. Epidemiology, pathogenesis, clinical symptoms, diagnostics, and treatment of Takotsubo syndrome are described.